The Political Education of Novice Voters among The Students of SMAN 1 Tinambung - Dewi Nuraliah (Lembaga Penelitian Pengabdian kepada Masyarakat, 2024)
The political education of novice voters for high school students is the first step taken to foster a correct understanding of politics related to general elections. This is considered to positively impact the political practice that students will carry out in the future. There are several stages carried out: 1) Implementation of Community Service in the form of presenting material to beginner voters for students; 2) Sharing sessions regarding political education. Implementation of activities is carried out using offline methods. The community service held at SMAN 1 Tinambung aims to enable students to participate in the 2024 general election as first-time voters actively. The results of community service in the form of workshops and sharing sessions related to politics, provide students with a basic understanding of politics, political literacy, and correct political practices. Keywords: election, political practices, political literacy, novice voters.